Land use/land cover change and its implication on soil erosion in an ecologically sensitive Himachal Himalayan watershed, Northern India - Prashanth, Manthena; Kumar, Arun; Dhar, Sunil; Verma, Omkar; Rai, Shashi Kant; Kouser, Beena (Frontiers in Forests and Global Change, 2023)
Soil erosion is a major environmental problem that affects land and w ater resources. It has many negative implications that lead to deforestation, poor agricultural practices, loss of soil fertility, and siltation that hinder socio-economic development. In view of this, the present study was conducted with the aim of estimating soil loss in relation to long-term land use/land cover change (LULC) in the Dehar watershed, Himachal Himalaya, North India. The study was carried out using Landsat and Sentinel imageries for the years 1999, 2010, and 2020. A GIS-based Revised Universal Soil Loss Equation (RUSLE) model was applied to assess the potential soil risk. The parameters used as input for computing the spatiotemporal changes of soil loss were rainfall erosivity, soil erodibility, topographic, crop management, and conservation support practice factors. The results showed a mean soil loss of 63.71, 60.99, and 66.71 t/ha/yr for the years 1999, 2010, and 2020, respectively. In the LULC class defined as Built-up Land, the mean soil loss decreased from 32.19 t/ha/yr in 1999 to 18.77 t/ha/yr in 2010, and in the year 2020 the mean soil loss slightly increased to 20.15 t/ha/yr. Moreover, the LULC class Barren Land registered a decrease in mean soil loss for the years 1999, 2010, and 2020 of 86.43, 74.60, and 73.19 t/ha/yr, respectively. Regarding the Agriculture Land class, the rate of mean soil loss slightly increased from 32.55 t/ha/yr in 1999 to 33.35 t/ha/yr in 2010, and the mean soil loss decreased to 25.43 t/ha/yr in the year 2020. Areas covered under Forest Land experienced an increase in mean soil loss from 65.30 t/ha/yr in 1999 to 65.87 in 2010 and 74.72 t/ha/yr in 2020. The study demonstrated that LULC changes apparently influenced the soil loss in the Dehar watershed. Therefore, urgent interventions are required with the involvement of scientists, policymakers, and the general public for conservation and management of soil resources.